The Regulation of Skeletal Muscle Alanine and Glutamine Formation and Release in Experimental Chronic Uremia in the Rat: SUBSENSITIVITY OF ADENYLATE CYCLASE AND AMINO ACID RELEASE TO EPINEPHRINE AND SEROTONIN - Garber, Alan J. (1978)
The mechanism of the increased alanine and glutamine formation and release from skeletal muscle in experimental uremia was investigated using epitrochlearis preparations from control and chronically uremic rats. In uremic muscle, insensitivity to epinephrine or serotonin suppression of alanine and glutamine release was observed. With control muscles, 1 nm or greater, epinephrine inhibited alanine and glutamine release, whereas with uremic muscles, epinephrine concentrations <1 μM did not alter amino acid release. Decreased alanine and glutamine release with 1 nM serotonin was observed in control muscles, but no inhibition was observed with concentrations <1 μM in uremic muscle. Muscle amino acid levels were the same in control and uremic muscles in the presence or absence of epinephrine or serotonin. The reutilization of released alanine by protein synthesis or oxidation to CO(2) was not differentially affected by epinephrine in uremic muscles as compared with control muscle. Dibutyryl-cAMP inhibited amino acid release equally in uremic and control muscles. Epinephrine or serotonin increased cAMP levels two- to four-fold or more in control than in uremic muscle. Basal- and fluoride-stimulated adenylate cyclase activities were equal in uremic and control muscle homogenates and in membrane fractions, but 10 μM epinephrine-stimulated adenylate cyclase was reduced 30-60% with uremia. At any concentration of epinephrine (0.001—100 μM), the stimulation of membrane adenylate cyclase activity was one- to twofold greater with control membranes than with uremic muscle membranes. With either control or uremic muscle, peak adenylate cyclase activity was observed at 1 μM epinephrine. These data indicate that skeletal muscle in chronic uremia acquires an insensitivity to the metabolic action of epinephrine or serotonin. This insensitivity may be attributable in part to the diminished increments in muscle cAMP levels produced by adrenergic and serotonergic agonists. The decreased cAMP levels may derive in turn from a decreased activity or subsensitization of the agonist-stimulated adenylate cyclase in uremic muscle.